Ácido desoxicólico na redução da gordura submentual: avaliação da eficácia, segurança e viés de patrocínio da indústria - Inocêncio, Gabriel Santiago Giuglio (2022)
Objective: To evaluate the efficacy of deoxycholic acid in reducing submental fat and assess the measures of safety results and industry sponsorship. Methodology: A systematic review was performed according to the PRISMA recommendations for describing the study, and a protocol was registered in the PROSPERO database. Seven main databases (MedLine via PubMed, SciELO, LILACS, Embase, Scopus, Web of Science, and the Cochrane Library) were extensively searched. The OpenGrey, OpenThesis, and OATD databases partially searched the gray literature. Randomized controlled trials were included in this review without restrictions on language and year of publication. Two reviewers extracted the data and assessed the individual risk of bias in the eligible studies with the Cochrane Collaboration's Risk of Bias Tool (RoB, version 2.0). The industry sponsorship bias was evaluated according to citations in the articles regarding industry funding/sponsorship throughout the texts, the presence of a conflict of interest statement, acknowledgments, and connections between the authors and the industry that manufactures the product. Results: The initial search resulted in 5756 titles, of which only five met the eligibility criteria and were included in the qualitative analysis and meta-analysis. The studies were published between 2014 and 2019. Only two studies had a low risk of bias for efficacy and safety results. When assessing the industry sponsorship bias, all studies reported having received funding or sponsorship from companies and explained the type of sponsorship. According to the meta-analysis, patients treated with deoxycholic acid showed significant positive results for all efficacy outcomes and a higher risk of fibrosis, pain, erythema, numbness, swelling, edema, pruritus, nodules, headache, and paresthesia. Conclusions: Based on low and moderate certainty of evidence, the studies showed a positive effect regarding the efficacy of deoxycholic acid, regardless of the dose. There were adverse effects of low magnitude and very tolerable. All studies showed industry sponsorship bias. Independent clinical studies are encouraged.